Postural balance ability and vertical jumping performance in female veteran volleyball athletes and non-athletes - Nikolaidou, Maria-Elissavet; Sotiropoulos, Konstantinos; Barzouka, Karolina (Frontiers in Sports and Active Living, 2023)
Lifetime participation in sports is associated with improved components of physical conditioning. The main purpose was to cross-sectionally investigate postural balance and vertical jumping performance in athletes with different histories of sports participation and secondarily to examine the restriction of vision on balance ability. A final aim was to investigate possible associations between balance and jumping performance. We hypothesized higher balance and jumping performance in active veteran volleyball athletes compared to retired athletes and non-athletes, suggesting a positive effect of continuous systematic training in active veteran athletes. We also hypothesized greater negative effect of vision removal on balance in the veteran compared to non-athletes due to athletes' stronger reliance on visual information. Eighty-one healthy middle-aged women (mean (standard deviation) 50 (5) years) were assigned to three experimental groups, a retired (n = 39, recreationally active former athletes), an active (n = 27, training 2days/week x 1.5 h/session) veteran volleyball athletes' and a control group (n = 15, sedentary participants). Participants completed an assessment of single-legged quiet stance trials with either left or right leg with eyes open while standing barefoot on a force plate and two-legged trials with both eyes open or closed. They also executed a protocol of countermovement jumps. Statistical analyses included univariate and full factorial ANOVAs with group and vision as fixed and repeated-measures factors and simple linear regression analysis. In the single-legged balance task, solely the mediolateral sway range was greater for the active (p < 0.001) and retired athletes (p < 0.001) compared to non-athletes, whereas in the two-legged stance, no differences among groups were found (p > 0.05). Restriction of vision deteriorated balance performance similarly in the three groups as a significant vision effect was found for path length (p < 0.001), anteroposterior (p < 0.001) and mediolateral sway (p < 0.05). The active and retired athletes had significantly (p < 0.001) greater height, mean and maximal power in countermovement jump compared to non-athletes. Results showed weak associations (average R2 = 9.5%) of balance with jumping performance only in the veteran volleyball athletes' group. Overall, the findings showed that retired volleyball athletes exhibited similar balance ability and vertical jumping performance as the active ones, suggesting a positive impact of prior experience in systematic training.